The Role of a Pragmatic Approach in the Habituation of Spoken Standard Indonesian to Enhance Elementary School Students’ Public Speaking Skills: a Systematic Literature Review - Elma Nur Hafizah; Aninditya Sri Nugraheni; Abroto (Yayasan Ilomata, 2026)
Public speaking competence among elementary school students remains constrained by psychological barriers, including anxiety, low self-confidence, and limited mastery of standard oral Indonesian. In classroom interaction, standard Indonesian is often perceived as overly formal and disconnected from students’ everyday communication practices, which reduces its functional use in authentic researchs. From the perspective of communicative competence and pragmatic theory, this condition reflects a gap between linguistic knowledge and the ability to apply language appropriately in research-sensitive oral communication. This study aims to synthesize the contribution of pragmatic aspects to the habituation of standard oral Indonesian and to examine their pedagogical implications for students’ public speaking development. A Systematic Literature Review (SLR) design was employed, analyzing 12 peer-reviewed studies indexed in Scopus and ProQuest published between 2016 and 2026. The selection process followed explicit inclusion criteria, prioritizing elementary-level studies while incorporating a limited number of comparative studies from other educational levels to strengthen conceptual generalization. A thematic synthesis approach was applied to identify recurring instructional strategies, pragmatic components, and reported learning outcomes. The findings suggest that teacher modeling, researchualized dialogue practice, and simulation-based learning are consistently associated with increased student engagement in using standard oral Indonesian. Pragmatic elements, such as politeness strategies, deixis, speech acts, and prosodic features, are also linked to improved communicative appropriateness and reduced speaking anxiety. However, these results indicate patterns of association rather than causal relationships due to the heterogeneity of the included studies.